STRATEGI PEMASARAN ISLAMI DALAM MENINGKATKAN PENJUALAN PADA BUTIK CALISTA - Mubarok, Nurul (I-Economics, 2017)
Boutique "Calista" is one of Muslim clothing company in Palembang city. Where usually a company that has a perception of movement of all components of the company in the context of implementation of the parent strategy and operational strategies, objectives and targets set to achieve. This research aims to find out the Islamic marketing strategy here which consists of several characteristics. To recognize market characteristics and market structure is very advantageous for companies to remain competitive and survive. The weaknesses and advantages of the company should be analyzed to become a strong starting point for the company in making effective and efficient decisions and to strengthen its position from existing competitors. In his financial statements at the Calista boutique is experiencing an increase in sales decline. And analyzed using qualitative data analysis method. By way of interviewing the informants boutique Calista. Field research procedure that produces descriptive data, in the form of written or oral data of people or observed behavior. Therefore in this study any symptoms associated with Islamic marketing at Calista Boutique will be thoroughly and thoroughly examined and attempted to give a deep meaning of the phenomena found. From the research results can be reviewed from the perspective of Islamic marketing strategy, Calista Boutique in addition to applying the theory and concept of conventional marketing strategy, also apply Islamic marketing strategy consisting of three main points first, the application of Islamic marketing characteristics; Second, the application of Islamic business ethics, thirdly, follow the marketing practice of Prophet Muhammad SAW. Based on the nature of Prophet Muhammad SAW namely: Shiddiq, Amanah, Fathanah, and Tabligh.